Social Network and Organizational Leadership at the Higher Education Institution: A Case Study - Gugyh Susandy; Yanu Endar Prasetyo (Indonesian Journal of Sustainability Accounting and Management, 2019)
The roles of social network and informal leadership network are not only crucial to companies or government institutions, but also to the academic institutions. As the interaction within the organization becomes more complex and dynamic, there is a lack of knowledge of the overall picture of informal leadership network at the higher education institution. In this study, we conducted a comprehensive analysis of three types of social networks and informal leadership in Sekolah Tinggi Ilmu Ekonomi Sutaatmadja (STIESA). They are the information network in an internal organization, cooperation network in technical problem solving of the organization, and a personal support network in the organization. The method used in this research was survey and Social Network Analysis (SNA). The respondents in this research were the whole leaders and staffs of STIESA. The findings of this study classified the three social networks and informal leadership and built network matric to be further explored for the strategic decision-making process of the organization. Each type of social network and informal leadership, along with its characteristics, is discussed and explored.